Zinc wheat - Virk, Parminder (International Food Policy Research Institute, 2014)
We construct and compare three distinct measures of household asset wealth that complement traditional income‐ or expenditure‐based measures of socioeconomic status. We apply these measures to longitudinal household survey data from China and demonstrate that household asset wealth has been increasing over time, a theme consistent with many previous studies on the process of development in China. Unlike other studies that have shown rising income inequality over time, however, we show that asset wealth inequality has actually been declining in recent years, indicating widespread participation in the benefits of economic reforms. Furthermore, the evolution in the cumulative distribution of household welfare is such that social welfare has been increasing with the passage of time, despite rising inequality in the early years of the survey.